Management of Giant Cervical Teratoma with Intracranial Extension Diagnosed in Utero - Thawani, Jayesh P.; Randazzo, Michael J.; Singh, Nickpreet; Pisapia, Jared M.; Abdullah, Kalil G.; Storm, Phillip B. (Journal of Neurological Surgery Reports, 2016)
Cervical teratomas are rare germ cell tumors affecting the fetus that are associated with significant morbidity and mortality due to an increased risk of airway obstruction at delivery. These tumors can commonly produce polyhydramnios that results from the fetus' impaired ability to swallow amniotic fluid. Improved rates of prenatal diagnosis through comprehensive evaluations and imaging have dramatically impacted the perinatal management of infants with this condition. Here, we report a patient diagnosed with polyhydramnios whose fetus was discovered to have a giant cervical teratoma on imaging studies. The child underwent surgical resection after having the airway secured under the uteroplacental support as part of an ex utero intrapartum treatment procedure performed at 37 weeks. The following gross pathological and magnetic resonance images demonstrate this condition and its currently accepted treatment.
Keywords: cervical teratoma; EXIT procedure; perinatal management; polyhydramnios